Β‐CsCu5Se3: A Promising Thermoelectric Material going beyond Photovoltaic Application. Issue 11 (4th October 2020) - Chen, Yanyan; Shen, Yupeng; Li, Xiaoyin; Sun, Jie; Wang, Qian
Abstract: Copper chalcogenides have attracted much attention in recent years because of their promising applications in thermoelectric conversion. However, many of them suffer from phase transformation at low temperature. Motivated by the synthesis of bulk β ‐CsCu5 Se3 with high phase transformation temperature of 923 K for photovoltaic applications, its thermoelectric properties using first‐principles calculations combined with Boltzmann transport theory are systematically studied. The results show that β ‐CsCu5 Se3 possesses ultralow lattice thermal conductivities of 0.24, 0.41, and 0.25 W mK −1 along the x, y, and z directions at room temperature, respectively, which are further reduced to 0.09, 0.15, and 0.09 W mK −1 at 800 K. A detailed analysis of its group velocity, three phonon scattering rate, Grüneisen parameter and three phonon phase space reveals that the weak harmonicity and strong phonon anharmonic scattering are responsible for the ultralow lattice thermal conductivity, leading to a high figure of merit ( ZT ) value of 1.81 along the y direction at 800 K, which is three times higher than that of known thermoelectric materials o ‐CsCu5 S3 (0.46 at 800 K) and t ‐CsCu5 S3 (0.56 at 875 K). This study suggests that β ‐CsCu5 Se3 is a multifunctional material promising for both photovoltaic and thermoelectric applications. Abstract : A recently synthesized photovoltaic material, β ‐CsCu5 Se3, is found to exhibit good thermoelectric performance with a high ZT value of 1.81 in the y direction at 800 K.